The GEF-6 Biodiversity Strategy - Global Environment Facility (World Bank Group, Washington, DC, 2014)
The Convention on Biological Diversity (CBD) defines biodiversity as the variability among living organisms from all sources including, inter alia, terrestrial, marine and other aquatic ecosystems and the ecological complexes of which they are part; this includes diversity within species, between species, and of ecosystems. The Millennium Ecosystem Assessment and TEEB (The Economics of Ecosystems and Biodiversity) demonstrated that biodiversity underpins ecosystem goods and services that are required for the survival of human societies and for the future of all life on the planet. In addition, biodiversity generates considerable economic value through the provision of goods such as food, water, and materials, and services such as climate regulation, pollination, disaster protection, and nutrient cycling. Governments, civil society organizations, the private sector, indigenous people and local communities, and others have made some progress in sustainably managing biodiversity and ecosystems at local and national levels, but not at the scale necessary to stem the ongoing tide of biodiversity loss globally. Current estimates indicate that species loss is occurring at 1,000 to 10,000 times the natural background rate. Of all the global environmental problems the world is facing today, biodiversity loss is the only one that is likely irreversible.